Patella component diameters of 38 mm and up might be associated with higher revision rates after patella resurfacing - Anna Jungwirth-Weinberger; Kilian List; Ulrich Bechler; Carola Hanreich; Stefan Rueckl; Friedrich Boettner (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Purpose Patellar resurfacing is considered the standard of care for total knee arthroplasty in the USA. Complications of patella resurfacing include aseptic loosening or patella fractures and can threaten the integrity of the extensor mechanism. The goal of this study was to report on patella button revision rates in posterior stabilized total knee arthroplasty. Material and methods Between 01/2010 and 08/2016 patella buttons were implanted in 1056 patients (267 men and 550 women) as part of a posterior stabilized total knee arthroplasty. Results Of 1056 cases, 35 cases (14 women, 15 men, 5 bilateral, 3.3%) showed early loosening at a mean 52.5 months postoperatively. Patella components of 38 mm or larger diameters showed a significantly higher loosening rate than the 29, 32, 35 mm buttons (p < 0.01). Mean BMI of patients identified with aseptic loosening was 31.7 kg/m2, mean age at time of revision surgery was 63.3 years. All of the patients with loosening of the patella button required revision surgery; in 33 cases an exchange of the button was performed, in two cases a removal of the button and patellar bone grafting was indicated. No complications occurred after revision surgery. Conclusion The current study reports a 3.3% patella loosening rate during this mid-term follow-up. Size 38 mm and larger patella components showed a significantly higher revision rate than smaller buttons and the authors advise caution when using large diameter patella components.